Editorial Thematik Dossie (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Information on the content of the Thematic Dossie: Artes vivas e o Antropoceno/Capitaloceno II
Keywords: editorial; articles; thematic dossiers